2018
DOI: 10.3892/or.2018.6894
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the growth of tumor cells under chronic stress via the ADRB‑2‑HIF‑1α axis

Abstract: Resveratrol is a type of polyphenol that is abundantly present in knotweed and grapes, and has been confirmed to have tumor-inhibitory properties. However, the effect of resveratrol on tumor cells under chronic stress conditions remains unclear. The aim of the present study was to demonstrate that resveratrol exerts a significant inhibitory effect on the growth and proliferation of tumor cells under chronic stress in a dose-dependent manner. Furthermore, resveratrol was able to induce apoptosis of cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Rather, we demonstrate that preventing HIF-1α drop restores the correct desensitization cascade of BAR2, indicating a link between HIF-1 and BAR2 upregulation. In this respect, the growth of cancer cells under chronic stress appears to be regulated by the HIF-1/BAR2 axis as demonstrated by the finding that resveratrol inhibits the proliferation of chronically stressed cancer cells by preventing the upregulation of both HIF-1α and BAR2 [ 44 ]. Another possibility is that DMOG acts directly on BAR2 internalization without the intervention of HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we demonstrate that preventing HIF-1α drop restores the correct desensitization cascade of BAR2, indicating a link between HIF-1 and BAR2 upregulation. In this respect, the growth of cancer cells under chronic stress appears to be regulated by the HIF-1/BAR2 axis as demonstrated by the finding that resveratrol inhibits the proliferation of chronically stressed cancer cells by preventing the upregulation of both HIF-1α and BAR2 [ 44 ]. Another possibility is that DMOG acts directly on BAR2 internalization without the intervention of HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of resveratrol upon hypoxia have been mainly related to the transcription and protein accumulation of the hypoxia‐inducible factor 1‐alpha (HIF‐1α), which is induced by a lack of oxygen. The expression of HIF‐1α and cellular viability was diminished in HepG2 human hepatoblastoma cells, SKOV‐3 ovarian carcinoma cells, and BxPC‐3 human pancreatic cancer cells with resveratrol supplementation at 25 and 50 µM (Ma et al, ). Indeed, resveratrol (20 mg/kg of body weight) also decreases mRNA and protein levels of HIF‐1α in the liver of rats induced to an ischemia/reperfusion (Zhang, Li, Yu, & Wu, ).…”
Section: The Relationship Between the Cytotoxic Effect Of Resveratrolmentioning
confidence: 99%
“…Resveratrol cytotoxic effects have been reported in S. cerevisiae (Ramos‐Gomez et al, ), human lung adenocarcinoma ASTC‐a‐1 cells (Zhang, Wang, & Chen, ), human pancreatic Bx‐PC‐3 cancer cells (Ma et al, ), and rat B103 neuroblastoma cells (Rahman, Kim, Kim, Oh, & Huh, ). In addition, mitochondriotropic resveratrol derivatives showed strong cytotoxic effects in mouse colon cancer CT‐26 cells (Sassi, Mattarei, Azzolini, Bernardi, et al, ; Sassi, Mattarei, Azzolini, Szabo, et al, ), suggesting that the cytotoxic mechanism of resveratrol should be universal for several eukaryotic cells.…”
Section: The Relationship Between the Cytotoxic Effect Of Resveratrolmentioning
confidence: 99%
“…However, the upregulation of HIF-1α that is independent of hypoxia is still unclear. Previous studies showed that the expression of HIF-1α in tumor tissue increased under chronic stress (8)(9)(10)(11), and β2-AR-HIF-1α axis can regulate the stress-induced pancreatic tumor growth and angiogenesis (11). The relationship between psychological stress stimulation and hypoxia-independent HIF-1α pathway activation in tumors needs to be further clarified.…”
Section: Introductionmentioning
confidence: 97%